The Role of Religious Leaders in Resolving Conflict and Political Violence in Pilrio in Air Gemuruh Village, Jambi Province - Yayan Saputra; Asniah Asniah; Sefriyono Sefriyono (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2024)
This article discusses the role of religious leaders in overcoming political violence in Pilrios in Air Gemuruh Village. Religious leaders are essential in mobilizing community participation in an election. The success of religious figures in reconciling the political violence of the community in the election in the Air Gemuruh village area is determined mainly by the ability and style of religious figures in giving their political speeches. This is very interesting to elaborate further, so to see the relationship encourages this research to be carried out. This research uses qualitative research methods that are descriptive of the type of field research. Data collection by observation, interviews and documentation. Research findings show that the role of religious leaders in resolving and overcoming political violence is conducting intra-candidate dialogue, mediation and reconciliation, providing ethical and moral understanding, monitoring and monitoring elections and implementing election codes of ethics. The conclusion is the chronology of political violence caused by several crucial problems before the election's implementation, including setting dates. Second the issue of funding. Third, the conflict and practice of money politics. In the pre-implementation of the election, the Permanent Voters List (DPT) is first. Second is the neutrality of the bureaucracy and Civil Servants (PNS). Third, conflicts occur in the implementation of Pilrio in several regions with different scales and scopes. Fourth, lack of transparency. Fifth Pilrio result. Then the role of religious leaders in preventing and overcoming political violence is to convey the message of political peace and conduct political education.